IMPACT AND QUALITY OF PUBLIC SERVICES ON COMMUNITY SATISFACTION - Ashwad, Hajar; Teniro, Alwin; Efendi, Muhsin (Universitas Jenderal Ahmad Yani, 2025)
This research aims to analyze the impact of the quality of public services on community satisfaction in the Kute Panang District, Central Aceh Regency. The survey method was used to distribute questionnaires to 127 respondents to represent the people who live in the area. The data that has been collected is then processed, presented, and analyzed using non-parametric Chi-Square statistics with a significance level ???? = 0.05. The research results showed that the quality of public services with indicators of physical evidence, empathy, reliability, responsiveness, and guarantees positively and significantly affected public satisfaction. However, it was still found that 40.94% of the public rated the quality of service as